Analysis of public awareness and behaviour in Banjarmasin City towards reducing the use of plastic waste: a case study of environmentally friendly policy implementation - Hakim, Muthia Fitriana; Martono, Dwi Nowo; Agustina, Haruki (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Increased environmental awareness in Banjarmasin City has led to the implementation of a policy to reduce the use of single-use plastic bags. This study aims to evaluate people's behaviour related to the policy by focusing on three main variables: environmentally friendly attitudes, lifestyle, and knowledge about the dangers and benefits of reducing plastic waste. Methods: This study used a quantitative approach with data collected through questionnaires distributed to 155 respondents in Banjarmasin City. The questionnaire instrument was designed to measure people's environmentally friendly attitudes, lifestyles, and knowledge of the benefits and hazards of plastic waste. The data was analysed by calculating the mean score and frequency to assess the level of awareness and behaviour. Findings: The results of the analysis show that in general, the environmentally friendly attitudes of the people of Banjarmasin are quite good with an average score of 3.54, but there is a need to increase understanding and participation in reducing the use of plastic bags. The community's eco-friendly lifestyle obtained an average score of 3.35, indicating an area that needs improvement. The community's knowledge of the benefits of plastic waste reduction had an average score of 3.87, while knowledge of the dangers of plastic waste reached an average score of 3.90, signalling that the community already has a fairly good understanding of this issue. Conclusion: This study concludes that although the people of Banjarmasin have a good understanding of the dangers and benefits of plastic waste reduction, environmentally friendly attitudes and lifestyles still need to be improved. A more intensive education and socialisation programme is expected to increase compliance and participation in implementing the plastic bag reduction policy. Novelty/Originality of This Study: This study provides new insights into how plastic bag reduction policies are accepted and implemented at the community level, focusing on the relationship between knowledge, attitudes, and lifestyles. The study also highlights the importance of integrating environmental education in local policies to improve the effectiveness of plastic waste reduction.